Health and Demographic Surveillance Systems Within the Child Health and Mortality Prevention Surveillance Network. (9th October 2019) - Cunningham, Solveig A; Shaikh, Nida I; Nhacolo, Ariel; Raghunathan, Pratima L; Kotloff, Karen; Naser, Abu Mohd; Mengesha, Melkamu M; Adedini, Sunday A; Misore, Thomas; Onuwchekwa, Uma U; Worrell, Mary Claire; El Arifeen, Shams; et al.
Abstract: Health and demographic surveillance systems (HDSSs) provide a foundation for characterizing and defining priorities and strategies for improving population health. The Child Health and Mortality Prevention Surveillance (CHAMPS) project aims to inform policy to prevent child deaths through generating causes of death from surveillance data combined with innovative diagnostic and laboratory methods. Six of the 7 sites that constitute the CHAMPS network have active HDSSs: Mozambique, Mali, Ethiopia, Kenya, Bangladesh, and South Africa; the seventh, in Sierra Leone, is in the early planning stages. This article describes the network of CHAMPS HDSSs and their role in the CHAMPS project. To generate actionable health and demographic data to prevent child deaths, the network depends on reliable demographic surveillance, and the HDSSs play this crucial role.